Inflammatory bowel disease-like enteritis and caecitis in a senescence accelerated mouse P1/Yit strain. Issue 1 (1st July 1998) - Matsumoto, S; Okabe, Y; Setoyama, H; Takayama, K; Ohtsuka, J; Funahashi, H; Imaoka, A; Okada, Y; Umesaki, Y
Abstract : Background —A new subline of the senescence accelerated mouse (SAM) P1/Yit strain has been established which shows spontaneous enteric inflammation under specific pathogen free (SPF) conditions. Aims —To elucidate the pathogenesis of enteric inflammation in this new subline. Methods —The SPF and germ free (GF) SAMP1/Yit strains were used. Histological, immunological, and microbiological characterisation of the mice with enteric inflammation was performed. Results —Histologically, enteritic inflammation developed as a discontinuous lesion in the terminal ileum and caecum with the infiltration of many inflammatory cells after 10 weeks of age. The activity of myeloperoxidase, and both immunolocalisation and mRNA expression of inducible nitric oxide synthase increased in the lesion. CD3-ε positive T cells, neutrophils, and macrophages were more numerous in the inflamed mucosa of the SAMP1/Yit strain. The GF SAMP1/Yit strain did not show any inflammation in the intestinal wall, by the age of 30 weeks, and the enteritis and caecitis developed 10 weeks after the conventionalisation of the GF SAMP1/Yit strain. Conclusion —Enteric inflammation in the ileum and caecum developed in the SAMP1/Yit strain. The pathophysiological characteristics of the disease in this mouse have some similarities to those of human inflammatory bowel disease (IBD). This mouse strain should be a useful model system for elucidating the interaction between the pathogenesis of IBD and the gut microflora.